Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/ans.15035
|View full text |Cite
|
Sign up to set email alerts
|

Rates and outcomes of total knee replacement for rheumatoid arthritis compared to osteoarthritis

Abstract: Background Total knee replacement (TKR) has been shown to perform differently in patients with rheumatoid arthritis (RA) when compared to osteoarthritis (OA). In this study, we compare the survivorship between these two groups and examine patient and prosthesis factors that impact the revision rate. Methods All RA and OA patients undergoing TKR in Australia from 1 September 1999 to 31 December 2016 were included. Revision rates were assessed using Kaplan–Meier estimates of survivorship. The cumulative percent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 19 publications
(23 reference statements)
1
16
0
Order By: Relevance
“…Patients suffering from RA were shown to have higher rates of pulmonary disease, cardiac morbidity, and higher mortality after surgery [21, 22]. Although direct comparison of mortality between studies is difficult owing to differences in demographic data such as age, sex, medical comorbidity, and ethnic difference, mortality after TKA in patients with RA is higher than that in patients with OA [6, 7, 23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients suffering from RA were shown to have higher rates of pulmonary disease, cardiac morbidity, and higher mortality after surgery [21, 22]. Although direct comparison of mortality between studies is difficult owing to differences in demographic data such as age, sex, medical comorbidity, and ethnic difference, mortality after TKA in patients with RA is higher than that in patients with OA [6, 7, 23].…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to expect that, as RA progresses, most patients undergoing TKA will experience other joint physical disabilities and complications. Although several studies have reported on TKA results in RA patients, limited data are available on the long‐term follow‐up outcomes of TKA in patients with RA compared to those with OA [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of the authors' knowledge, there are no studies in the literature comparing mortality between patients with non-OA and OA preoperative diagnoses, although some studies have examined the impact of OA versus rheumatoid arthritis (RA) diagnoses on post-TKA mortality. 21 22 24 In an Australian study of 541,744 primary TKAs, Mooney et al 21 found that the rate of mortality between 0 and 5.5 years postoperative had a hazard ratio of 2.24 for patients with RA (95% CI: 2.06–2.46, p < 0.001) when compared with patients with OA. Our findings are consistent with this study, although the aforementioned study focused specifically on an RA diagnosis and longer-term mortality rather than all non-OA diagnoses and 30-day perioperative mortality measures.…”
Section: Discussionmentioning
confidence: 99%
“…5 9 10 11 12 13 14 Many comorbid conditions have also been associated with increased postoperative mortality, including disseminated cancer, 15 severe chronic kidney disease, 16 17 18 and hypoalbuminemia. 19 20 In addition, preoperative diagnoses may contribute to mortality rate, with studies finding that diagnoses such as rheumatoid arthritis 21 22 23 or osteoarthritis (OA) 24 are associated with increased risk of mortality. However, few studies have stratified mortality based on age, comorbidity burden, and preoperative diagnosis to elucidate mortality risk based on a specific patient's demographics and medical history.…”
mentioning
confidence: 99%
“…People younger than 60 y needing TKR often require surgery for trauma-induced OA or for rheumatoid arthritis, both of which may result in different clinical trajectories. 50,75 Evidence also suggests that younger adults may have higher expectations of TKR outcome and pain and functional recovery than older adults after surgery. 76 In addition, perceptions of pain and function may be influenced by reduced activity levels in older adults following TKR as compared with younger adults, 39 and higher rates of surgical complications in older adults.…”
Section: Sample Population (S)mentioning
confidence: 99%